Control of eta carbide formation in tungsten carbide powders sputter-coated with (Fe/Ni/Cr) - Fernandes, C. M. (2007)
Composite powders of tungsten carbide with variable coating contents of Fe/Ni/Cr based alloys (1-15 wt.%) were prepared by sputtering. The coated powders have revealed a good performance to shape-forming and sintering. However, the presence of nanocrystalline coatings could enhance the formation of a brittle phase during sintering, named [eta]-phase, (M, W)6C. To investigate this effect, the powders were heat-treated at variable temperatures, up to 1400 °C. For comparison, conventionally prepared powders were studied, too, and the content of [eta]-phase was found to be higher for the sputter-coated ones. This result is attributed to the content of binder elements with affinity to carbon, like chromium, enhanced by the difference on binder characteristics, such as nanocrystallinity and morphology. It was concluded that an effective control of the reaction can be achieved by increasing in the binder composition the ratio between the elements without affinity and those with affinity to carbon and/or enlarging the carbon content.